Profil Pohon Keluarga (Pedigree) Siswa Dengan Intellectual Disability (Id) Dan Multiple Congenital Anomaly (MCA) Di SLB Negeri Kendal - Hesty Wahyuningsih; Anggari Linda Destiana; Nura Eky Vikawati (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2020)
Pedigree construction is one of the ways to seek the inheritance pattern of disease. Three generations pedigree has many benefit in genetic counseling session particularly in establishing a specific inheritance pattern such as autosomal recessive or dominant. This research aimed to analyze three generations pedigree in the family of ID and MCA patients in the Special school of Kendal. This is a descriptive observational study using the interview method in 33 student guardians or parents of ID and MCA students. Twenty-five of 33 respondents collects the complete data. This study showed that three generations of pedigree construction of 8 respondents could not conclude the inheritance pattern. The data showed that two pedigree are suspect of chromosomal abnormalities in the presence of family history with similar disorder, family history with ID and MCA, and family history with IUFD or stillbirth. Further investigation using cytogenetics, FISH, and microarray is needed to establish the diagnosis